Appendicular Body Composition Analysis: Validity of Bioelectrical Impedance Analysis Compared With Dual-Energy X-Ray Absorptiometry in Division I College Athletes. Issue 11 (November 2019) - Brewer, Gabrielle J.; Blue, Malia N.M.; Hirsch, Katie R.; Peterjohn, Austin M.; Smith-Ryan, Abbie E.
Abstract : Abstract: Brewer, GJ, Blue, MNM, Hirsch, KR, Peterjohn, AM, and Smith-Ryan, AE. Appendicular body composition analysis: Validity of bioelectrical impedance analysis compared with dual-energy x-ray absorptiometry in Division I college athletes. J Strength Cond Res 33(11): 2920–2925, 2019—The purpose of this study was to evaluate validity of appendicular body composition measurements measured from a multifrequency bioelectrical impedance analysis (MF-BIA) compared with a dual-energy x-ray absorptiometry (DXA) criterion in Division I athletes. One hundred sixty male ( n = 44) and female ( n = 116) collegiate athletes were enrolled: Men's Cross Country ( n = 15), football linemen ( n = 29), Women's Soccer ( n = 27), Women's Field Hockey ( n = 27), Women's Cross Country ( n = 13), Women's Gymnastics ( n = 16), and Women's Lacrosse ( n = 33). Appendicular fat mass (FM) of the arms (AFM, right AFM, left AFM) and legs (LFM, right LFM, left LFM), appendicular fat-free mass (FFM) of the arms (AFFM, RAFFM, LAFFM) and legs (LFFM, RLFFM, LLFFM), total body FM and FFM, and total body %fat were collected from both devices. MF-BIA significantly underestimated appendicular FFM of the arms (AFFM mean difference [MD]: −0.7 kg; RAFFM: −0.4 kg; LAFFM: −0.4 kg, p < 0.001) and legs (LFFM MD: −3.8 kg; RLFFM: −1.9 kg; LLFFM: −1.9 kg, p < 0.001), and FM of the legs (LFM MD: −2.5 kg; RLFM: −1.3 kg; LLFM: −1.3 kg, p < 0.001). There was no significant difference in appendicular FM measures of the arms ( p = 0.174). All measures held true for male subjects and female subjects. Female subjects produced smaller differences compared with male subjects. The lack of validity, from raw and relative error, between the devices for most appendicular measures (FFM of arms and FFM and FM legs) and all total body measures (FM, FFM, and %fat) suggest that this MF-BIA may not be accurate in measuring a lean, athletic, population compared with DXA.